Influence of growth parameters on bacteriocin-like inhibitory substances (BLIS) production by lactic acid bacteria. (14th December 2022) - Foudjing, Gildas Gaëlle Domguia; Sarmast, Elham; Allahdad, Zahra; Salmieri, Stéphane; Lacroix, Monique
Abstract: This study aimed to investigate the possible production of bacteriocin-like inhibitory substances (BLIS) and optimize it by Lactobacillus sakei and combined Lactobacillus curvatus / Pediococcus acidilactici, lactic acid bacteria used for the meat fermentation. The effect of growth parameters on BLIS production was evaluated by measuring the antibacterial activity of the cell-free supernatant of these bacteria. The stability of the cell-free supernatant of combined L.curvatus / P.acidilactici bacteria was also examined after heat treatment and pH variations. Results showed highest BLIS production by L.curvatus / P.acidilactici was at growth temperatures of 28°C and pH 5, while the optimum condition for production of BLIS by L.sakei was 24°C and pH 6.5. The BLIS production by L. curvatus / P. acidilactici bacteria was greatly influenced by carbon and nitrogen sources. The antimicrobial activity of BLIS in supplemented De Man, Rosa, and Sharpe broth (MRS) was 2044.44 AU/mL, 4.84-fold greater than unsupplemented MRS. None of the carbon sources used in this study affected the BLIS production by the L.sakei, while pea peptone enhanced the antimicrobial activity and showed a value of 188.89 AU/mL, 1.47-fold greater than unsupplemented MRS. The characterization of the cell-free supernatant of L. curvatus / P. acidilactici bacteria showed the heat stability and activity of BLIS at pH 2–10.